PENINGKATAN SIKAP ILMIAH ANAK USIA DINI MELALUI PERMAINAN SAINS - Olua, Erna (Jurnal Panrita, 2022)
This study aims to improve the ability of early childhood scientific attitudes through science games in group B children of Tunas Dansari Dosay Kindergarten, Kamoung Dosay. The method used is a classroom action research method, using a research model from Kemmis and Taggart. The focus of the research is on the process of learning science in scientific attitude skills using science games by group B teachers at Tunas Dansari Dosay Kindergarten, Kampung Dosay. The instruments used in this research are Observation, Documentation and Field Notes. The data analysis technique used in this research is numerical and description. The results of the research showed that the children's ability to use science games increased from cycle I, action I to action 3 and continued in cycle II, action I to action 3, the scientific attitude ability of children in group B in Tunas Dansari Dosay Kindergarten, Kampung Dosay, increased. This is evidenced by an increase from the percentage before the action to after the action is carried out, namely before the action is 34.8%, there is an increase in the first cycle, it is proven that the initial condition of scientific ability is 34.8%, through cycle 1 action 1 to action 8 increased to 51.5%, in the second cycle of action 1 to action 8, the child's ability increased to 63.5%, in the second cycle of action 2, so as to achieve the minimum completeness criteria